SOIL CHARACTERISTICS OF UDIPSAMMENTS AND LAND SUITABILITY EVALUATION FOR MAIZE IN THE ALAS RIVER RIPARIAN ZONE, ACEH TENGGARA - Irfan Apandi; Diapari Siregar; Basyaruddin (RADJA PUBLIKA, 2025)
The increase in national corn demand has triggered the utilisation of marginal land, including riverbank areas. This study aims to identify soil characteristics and evaluate land suitability for corn (Zea mays L.) cultivation in the Alas River border area, Southeast Aceh Regency. The research method used is descriptive exploratory with field surveys through pedon (soil profile) creation and laboratory analysis of soil physical and chemical properties. Morphological observations showed soil profiles developed from fluvial sedimentation material with A1, A2, C, and R horizons. Based on USDA Soil Taxonomy, the soil at the study site was classified into the Entisol order, Psamments suborder, and Udipsamments great group, dominated by sand fractions (78.42%–89.30%). Chemical analysis results show that the soil has an acidic pH (4.53–4.86), very low organic carbon content (0.15%–0.71%), and low cation exchange capacity. Based on the matching method, the land suitability class for maize cultivation is determined as N1 (currently unsuitable) with the main limiting factors being shallow effective depth (30 cm), very sandy soil texture, acidic pH, and low organic matter content. However, land potential can be improved through appropriate management strategies, such as liming to raise pH and adding organic fertiliser to increase water and nutrient retention capacity.